Model-Based Testing: Where Does It Stand? - BINDER, ROBERT V.; LEGEARD, BRUNO; KRAMER, ANNE (Communications of the ACM, 2015)
The article presents the results of the 2014 MBT User Survey which asked participants to rate model-based testing (MBT) in terms of efficiency and effectiveness. Topics include the merits of a common MBT classification scheme, MBT's use for software development in industries such as information technology, web application, and communications, and whether MBT is compatible with manual testing. The article also discusses how MBT models often include system models, test models, and environment models.